The correlation between salah (prayers) and students’ academic performance / Che Haslina Abdullah… [et al.] - Abdullah, Che Haslina; Omar, Mahanim; Raja Berahim, Raja Rosila; Ab Latif, Nur Afiqah; Zulkifli, Che Nooryohana (2017)
Salah (prayers) is the second pillar of Islam and the most important spiritual practice for Muslims. Salah can bring success to a Muslim's life and by abandoning it, can lead to various problems in one‘s life. In this study, a total of 28 degree students of UiTM Pulau Pinang who have achieved Cumulative Grade Point Average (CGPA) below 2.5 were selected in this research. This study was conducted to determine the students‘ understanding of the importance of salah, their daily routines that have affected their salah, as well as the correlation between their performance of salah and academic performances. The study has shown that there were more male students who have experienced a decline in academic achievement due to their negligence in performing their salah. The reasons being are salah is considered less important and they occupied most of their time by playing games and surfing the Internet. The data also indicated that they have shown penitence and feeling embarrassed to Allah and confessed that the problem in their academic performances most probably occur due to wrath of Allah for their failure in performing prayers.